Efek pengelompokan lokasi bisnis kuliner terhadap volume penjualan dengan mediasi kesadaran merek - Matheo Sheva Hastono; Rafael Juan Chesna Tjoanda; Hari Minantyo (Jurnal Manajemen Maranatha, 2025)
The food and beverage industry are a growing sector, and this growth prompts the majority of businesses in the industry to seek out new ways to gain customers' attention and increase their income. This makes the F&B industry as one of the most significant contributors to a country’s economic growth. This research aims to analyse the impact of location clustering of F&B businesses on their sales volume within the perimeter of DP Mall semarang, using brand awareness as a mediating variable, to see whether clustering has a positive or negative impact on these businesses. The research method used is quantitative, based on partial least squares-structural equation modeling (PLS-SEM) with a purposive sampling technique. Data was collected using a Lickert scale questionnaire from 123 respondents who met the selection criteria. The results of this research show a significant positive impact of the clustering of food and beverage businesses on their sales volume and confirm the significance of brand awareness as a mediator. The conclusion indicates that clustering F&B tenants in shopping centers can be an effective approach to increase their sales volume through the mediation of brand awareness, generating profits from the spillover effect. This research provides an understanding of how tenant location arrangements in shopping centers can increase profit for tenants within the culinary clusters. Further research is required to gain more information regarding qualitative perspectives and to explore the effect of it on different industries.